Earth, Empire and Sacred Text Muslims and Christians as Trustees of Creation. - Johnston, David L. (London : Equinox Pub., 2010)
Earth, Empire and Sacred Text examines the Muslim-Christian theology of creation and humanity, aiming to construct a dialogue to enable both faiths to work together to preserve our planet, to bring justice to its most needy inhabitants, and to contribute to peace-building.
Cover; Contents; Foreword; Acknowledgments; List of Figures; Introduction; PART I; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; PART II; Chapter 6; Chapter 7; Chapter 8; Chapter 9; Chapter 10; PART III; Chapter 11; Chapter 12; Appendix A; Appendix B; Appendix C; Appendix D; Bibliography; Indexes; Index of Biblical and Qur'anic References; Index of Authors; Index of Subjects.
Description based on print version record.
Keywords: Christianity and other religions -- Islam; Creation (Islam); Creation; Ecology -- Religious aspects -- Christianity; Ecology -- Religious aspects -- Islam; Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Creation (Islam); Creation; Ecology -- Religious aspects -- Christianity; Ecology -- Religious aspects -- Islam; Islam -- Relations -- Christianity; RELIGION / Islam / Theology; MUSIC / Printed Music / Musicals, Film & TV; Electronic books